Pollution Study And Bioremediation Of Heavy Metal In Aqueous And Sediment Phases Of Sungai Pinang River Basin - Saad, Farah Naemah Mohd (2013)
Sungai Pinang is known as one of the most polluted river in Malaysia. A study was conducted to verify the status of the water quality in Sungai Pinang and its tributaries. Eight sampling locations which located just before the meeting of each tributary were selected. The physical and chemical characteristics of water and sediment of each sampling sites were determined. Several variations in the results show that the water quality of Sungai Pinang and its tributaries are mainly due to season, sampling location and parameter tested. Better water quality index is achieved during rainy period compared to dry season. According to water quality index and Interim Water Quality Standards of Malaysia (INWQS), the water quality of the river fall within Class III to V for DO, BOD5, COD and AN while TDS, TSS, pH and EC fall between Class I and II. The temperatures of the waters during both seasons were at the normal range whilst the turbidity of the rivers was in Class II to IV. An evaluation on sediment characteristics and quality showed that the particle size distribution of the rivers were high with sand and a brief of silt and clay near to the river mouth. The results also revealed that the pH of the sediment were acidic except for Sungai Pinang which was slightly alkaline. Other chemical parameters for the sediments which are TOC, moisture content and TKN were high at several sampling locations while low PO4 3- concentrations was determined. Detailed surveys as well as referring to secondary data were also carried out to identify the key problems of each area with respect to land use. Four groups of river polluters affecting the quality of the river water within Sungai Pinang were identified which are firstly, sullage waters generated from domestic, wet markets, commercials and trades and abattoir, secondly, the sewage wastewater, thirdly, industrial effluents and fourthly, discriminant dumping of wastes into the rivers.